Treatment of epidermal growth factor receptor antagonist-induced skin rash: results of a survey among German oncologists - Hassel, Jessica C.; Kripp, Melanie; Batran, Salah-Eddin al-; Hofheinz, Ralf-Dieter (Onkologie, 2010)
Background: Skin toxicities are frequent in patients receiving epidermal growth factor receptor (EGFR) antagonists. Grading and management of these skin reactions are poorly standardized. Materials and Methods: We conducted a survey among German oncologists using a 7-item questionnaire distributed by e-mail via the working groups Internistische Onkologie (AIO) and Dermatologische Onkologie (ADO). The oncologists were provided with pictures and history of a patient with an acneiform rash and were asked to provide information on grading and treatment strategies. Results: 106 medical oncologists and 43 dermatooncologists responded to the survey. The scoring of the skin rash was indicated as follows (National Cancer Institute common toxicity criteria (NCICTC) grades 1/2/3;%): 10/59/31. 22% of the polled medical oncologists use preemptive treatment of skin rash. In the presented case, 91% chose local treatment with mainly hydrocortisone or antibiotic cream, and 64% chose systemic treatment with an antibiotic or isotretinoin. Only 9% of the medical oncologists would have referred the patient to a dermatologist. Dermatooncologists used more local antibiotics (p = 0.006) and rather less local steroids (p = 0.199). With regard to systemic treatment, dermatooncologists more often used isotretinoin (p = 0.002). In addition, dermatooncologists less often delayed cetuximab treatment because of skin toxicity (p = 0.009). Conclusions: The results of the present analysis illustrate that grading and treatment of EGFR antagonistinduced skin toxicities are very heterogeneous. Clearly, more randomized trials and a simple and reliable grading system are warranted.
Gesehen am 27.03.2023